Dynamics of Fibre Formation and Processing Modelling and Application in Fibre and Textile Industry - Beyreuther, Roland. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
The book deals with the modelling of steady state and non-steady state basic processes of fibre formation and fibre processing. Focal points are melt spinning processes (polymers and glass, drawing, spunbonded nonwoven), spun yarn spinning processes (drafting, carding) and the description of the dynamics in different process steps during the fibre processing (fibre transport, fibre heating and cooling, false twist texturing). A special chapter deals with dynamics of tensile force (measuring and evaluation possibilities) and its importance for the process stability. All presented examples are based on industrial practice and give the reader a direct imagination of the discussed problems. The results are explained in a userfriendly way and give the practitioner the possibility to optimize his or her own processing. The book will be of special interest to researchers, and engineers, in the man-made fibre and textile industry as well as to teachers and students of the relevant graduated and undergraduated courses in textile engineering and polymer physics including the accessory mechanical engineering.